An Analysis of Inhibiting Factors Affecting Thesis Completion among Students in the Informatics Engineering Education Program - Lature, Putri Yani; Rizkayeni Marta; Lativa Mursyida; Agariadne Dwinggo Samala (Jurnal Vokasi Teknik Informatika, 2025)
Delays in undergraduate thesis completion are a persistent issue in higher education, particularly within the Informatics Engineering Education Study Program at Universitas Negeri Padang. While prior studies have explored general academic barriers, limited research has systematically quantified the internal and external factors that hinder thesis progress in this specific context. This study addresses this gap by identifying and analyzing the dominant factors contributing to thesis delays using a quantitative approach supported by Confirmatory Factor Analysis (CFA). Data were collected through structured surveys distributed to final-year students. The analysis revealed six key influencing factors: motivation, thesis writing ability, health conditions, family support, supervisor guidance, and peer influence. Among these, motivation and writing ability were identified as the most dominant, with a combined variance contribution of 0.932. The novelty of this study lies in its integrated factor-based model that quantitatively distinguishes between internal and external constraints. These findings offer a practical foundation for targeted academic interventions and policy development aimed at accelerating thesis completion rates in vocational informatics education.